The Impact of Criminal Justice Administration on the Penal Sanction - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 1992)
One of the central philosophies underlying the Report of the Royal Commission into NSW Prisons is revealed in the widely quoted aphorism, "A person is sent to prison as punishment, not for punishment". The conditions under which prisoners are contained feature crucially in assessing both the perceptions and reality of prison as a punishment. Expectations for the experience of imprisonment vary enormously. These expectations in many particular forms have been used to justify the expansion and diversification of the penal sanction. In their most modest representation, however, it is hoped that "by treating all prisoners humanely in a manner befitting their human dignity ... prisoners will at least leave prison no worse than when they entered it".